Importance of urban plans and open spaces for urban sustainability: study in the city of Teresina, Piauí (Research, Society and Development, 2020)
With population growth, linked to the increase in urban problems, there is a concern in the planning and management of cities, focused on issues related to the environment and sustainability. The Global Agenda 21 defined guidelines for the construction of a more sustainable development, establishing strategies that should be inserted in the public policies of urban planning of each country, consolidating legislation related to the environmental issue and urban planning, such as the City Statute, which provided for the elaboration of a Master Plan. In this context, the city of Teresina, capital of Piauí, was in the process of preparing its Local Agenda 21, called Teresina Agenda 2015, established in 2002, and adopted as a Master Plan in the same year. In this work, it is proposed to analyze public open spaces in Teresina, as a result of the guidelines and actions of Agenda 2015, the Sustainable Development plan - Teresina Agenda 2015 and the 2006 Master Plan, identifying guidelines, strategies and policies contained in these plans, which acted in the creation, recovery and / or preservation of said spaces, considering the time frame between 2006 and 2019. As a methodology, bibliographic and documentary research was carried out, addressing urban planning policies, environmental policies and the preservation and protection of natural and urban landscapes. In addition, visits were made to selected free spaces, in order to analyze and obtain graphic records, using maps and photographs. It was observed that most of the established guidelines were not complied with, impairing the preservation, maintenance, structuring and security of free spaces in the city, resulting in places that are not very attractive to population.